神経炎症及び神経変性を管理するための方法及び組成物 (2019)
本開示は、神経炎症及び神経炎症媒介の神経変性疾患又は神経変性障害を管理するための方法及び組成物に関する。 A method of inhibiting neuroinflammation in neuron surrounding cells, includes a step of treating the neuron surrounding cells with at least one tyrosine kinase inhibitor or sirtuin-2 inhibitor or a combination thereof, to inhibit the neuroinflammation. A method of managing neuroinflammation or neuroinflammation mediated neurodegenerative disease or disorder in a subject in need thereof, includes administering at least one tyrosine kinase inhibitor or sirtuin-2 inhibitor or a combination thereof to the subject. A composition includes at least one tyrosine kinase inhibitor or at least one sirtuin-2 inhibitor optionally along with pharmaceutically acceptable excipient.